Tuberculous Peritonitis Associated with Ovarian Teratoma Presenting as Peritoneal Carcinomatosis - Chun-Yuan Su; Yuh-Cheng Yang; Chin-Yuan Tzen; Jen-Ruei Chen (Elsevier, 2005)
Objective: Peritoneal tuberculosis (TB) is a fatal disease if not promptly diagnosed. We present a case of unexplained ascites with miliary peritoneal TB and a review of the literature. Case Report: A 56-year-old woman was admitted to our hospital because of severe abdominal fullness for 20 days. Computed tomography scans of the abdomen showed massive ascites and a huge intrapelvic mass mimicking an ovarian dermoid cyst. Laboratory examinations revealed an elevated serum cancer antigen 125 level of 1,132.9 IU/mL and normal chest roentgenographic findings. About 5 L of ascitic fluid and many superficial whitish miliary deposits on the intra-abdominal and pelvic surfaces were found during exploratory laparotomy. A right ovarian cystic mass measuring 15 × 14 × 10 cm in size was noted and removed. Pathologic studies of the cyst revealed a mature cystic teratoma, and all the specimens from the peritoneum and the ovarian surface had chronic granulomatous inflammation with central caseous necrosis compatible with TB. She received postoperative anti-TB chemotherapy and was doing well 5 months after surgery. Conclusion: Tuberculous peritonitis is not easy to diagnose. We suggest that tuberculous peritonitis associated with ovarian teratoma should be included in the differential diagnosis of peritoneal carcinomatosis.